Rockfall Characterization and Structural Protection in the Siddhababa Section of Siddhartha Highway H10, Nepal - Gnyawali, Kaushal Raj; Shrestha, Ranjit; Bhattarai, Anil; Magar, Pramod Rangu; Dhungana, Anup Raj; Sukupayo, Imjal; Dumaru, Rasla (Journal of the Institute of Engineering, 2016)
Many national highways of Nepal are periodically facing the rockfall events, causing fatal accidents. The Siddhababa section of Siddhartha Highway is a lively example of an active rockfall zone where the highly steep slope geometry in combination to the unfavourable inclination of the rock joints with the road alignment primarily cause the rockfall. Recent accidents of a jeep and a bus have created much concern on rockfall in the area. But still, we do not possess any type of structural countermeasure to overcome this scenario. To address this problem, our study aims at frstly characterizing the rockfall in the area and then on proposing structural countermeasure as rockfall barriers, rock netting and rockshed, and assisted with rock bolting, based on simulation studies and analysis of the rockfall scenario in Rocscience Rocfall® program. Journal of the Institute of Engineering, 2015, 11(1): 1-11